2021
DOI: 10.1002/anie.202100349
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between a Foldamer Helix and a Macrocycle in a Foldarotaxane Architecture

Abstract: The design and synthesis of a novel rotaxane/ foldaxane hybrid architecture is reported. The winding of an aromatic oligoamide helix host around a dumbbell-shaped thread-like guest, or axle, already surrounded by a macrocycle was evidenced by NMR spectroscopy and X-ray crystallography. The process proved to depend on the position of the macrocycle along the axle and the associated steric hindrance. The macrocycle thus behaves as a switchable shield that modulates the affinity of the helix for the axle. Recipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Recently, we reported the formation of a foldarotaxane architecture consisting in a [2]rotaxane, the axle of which is also wrapped by a foldamer helix. 12 We showed that the winding of the helix around the encircled axle can be altered by the macrocycle localisation. Here, we investigate the reciprocal effect.…”
mentioning
confidence: 87%
“…Recently, we reported the formation of a foldarotaxane architecture consisting in a [2]rotaxane, the axle of which is also wrapped by a foldamer helix. 12 We showed that the winding of the helix around the encircled axle can be altered by the macrocycle localisation. Here, we investigate the reciprocal effect.…”
mentioning
confidence: 87%
“…Recent works exploited the fact that alkyl-carbamate rods that form foldaxanes may themselves be rotaxanes. 64 For instance, [2]rotaxane 20 (Figure 8C) possesses a dicarbamate binding station on which a helical foldamer may wind. It also contains an ammonium group as a binding site for a dibenzo-24-crown-8 (DB24C8) macrocycle.…”
Section: Effect Of Foldaxane Formation On Rodmentioning
confidence: 99%
“…In the past years, we have been focusing on the synthesis of several DB24C8‐based rotaxane molecular shuttles based on triazolium, [9] pyridinium amide, [10] amide, [11] Weinreb amide, [5b,d] amine and ketone [5d] moieties as more or less efficient secondary molecular stations for the DB24C8. Recently, we proposed the N ‐hydroxysuccinimide [5a,12] (NHS) and its NHS ester derivative [11,13] as thread's pseudo stoppers that allowed slippage of the DB24C8, on the one hand, and subsequent post‐synthetic [14] stopper exchange [5a,c,12a–b,13a,15] of rotaxane threads on the other hand. More precisely, NHS ester rotaxane building block was utilized as a precursor of a two‐station molecular shuttle containing a triazolium secondary station for the DB24C8 [13a] .…”
Section: Introductionmentioning
confidence: 99%
“…The control of the localization of the macrocycle along the encircled thread may be possible if the affinities between stations and macrocycle are different. Altering the affinities through chemical or physical stimuli , [6] or destabilizing a station‐macrocycle complex through intermolecular interaction, [5c,7] afforded a wide range of responsive rotaxanes molecular shuttles in the literature until now, with multiple miscellaneous applications [8] . In the past years, we have been focusing on the synthesis of several DB24C8‐based rotaxane molecular shuttles based on triazolium, [9] pyridinium amide, [10] amide, [11] Weinreb amide, [5b,d] amine and ketone [5d] moieties as more or less efficient secondary molecular stations for the DB24C8.…”
Section: Introductionmentioning
confidence: 99%